1999
DOI: 10.3109/07853899908995884
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Lyme borreliosis

Abstract: Lyme borreliosis is a worldwide family of tick-borne infections caused by the spirochete Borrelia burgdorferi sensu lato. It is the most common tick-borne human infection in the Western world. There are several subgroups of the spirochete. Two monovalent vaccines against this infection have been presented in the USA, both of which use the borrelial outer surface protein A (OspA) as antigen. The first of these vaccines has been released for general use. A European polyvalent vaccine using the antigen OspC is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In Eurasia, compared to the USA, a vaccine must be effective against all subgroups of the Borrelia spirochete. Some protective immunity against Borrelia infection in laboratory animals was demonstrated by other Borrelia burgdorferi proteins, for instance OspB and OspC 13,14 …”
Section: Treatmentmentioning
confidence: 99%
“…In Eurasia, compared to the USA, a vaccine must be effective against all subgroups of the Borrelia spirochete. Some protective immunity against Borrelia infection in laboratory animals was demonstrated by other Borrelia burgdorferi proteins, for instance OspB and OspC 13,14 …”
Section: Treatmentmentioning
confidence: 99%
“…However, recombinant unlipidated OspA was recognized by sera from patients with Lyme diseasẽ Dunn et al, 1990!, and further different studies suggested that recombinant OspA could be used to vaccinate humans against infection with B. burgdorferi spirochete~Fikrig et al, 1990;Simon et al, 1991!. Recently, effective andsafe OspA vaccines, with or without adjuvant, were released~Sigal, 1999;Wahlberg, 1999!. Hence, detailed knowledge of the immunological and molecular characteristics of OspA protein is important for the development of reliable diagnostic assays.…”
mentioning
confidence: 99%